THE CORRELATION OF TECHNOLOGY AND BUILDING VOCATIONAL INTEREST AND THE SUBJECT VOCATION SCORE OF GRADE X STUDENT AT SMK NEGERI 1 PADANG - 1930-1946 , Devky Auzan (CIVED, 2016)
ABSTRACTThis research was purposed to reveal the correlation of technology and building vocational interest and the subject  vocation score of grade X student at SMK Negeri 1 Padang.This research is correlational research with two variables, the sampling technique used was Proportional Random Sampling with 101 sample from 181 population. The data were 4 choices primary data were obtained by distributing questionnaires about technology and building vocational interest, mean while the secondary data were the overage subject vocation score such as basic drawing techniques, static and mechanic, building science, building material, and work safety science learned by the students Building Desain Engineering, Wood Construction Engineering, and Concrete Engineering. The data analysis techniques used were data verification, linearity test to prove that the data distribution was from normal and linear distributed sample, and hypothesis  test.The result of the analysis showed that there were low significant  correlation coefficient between technology and building vocational interest and the subject vocation  score of grade X students at SMK Negeri 1 Padang. It was observable by the coefficient pearson correlation score 0,268 ≥ Alpha (0,05), this result showed that there was correlation between technology and building vocational interest and the subject vocation score of grade X students at SMK Negeri 1 Padang. The Sig (2-tailed) score for 0,007 < Alpha (0,05) showed that there was significant correlation between technology and building vocational interest and the subject vaocation score of grade X students at SMK Negeri 1 Padang with 95% reliability level.  Keywords: vocational interest, learning outcome